ANALISIS FAKTOR YANG BERPENGARUH TERHADAP PERILAKU KEWARGANEGARAAN ORGANISASI PADA APARATUR DESA DI KABUPATEN KEBUMEN - Marynta Putri Pratama (Politeknik Sawunggalih Aji, 2019)
The purpose of this study is to analyze the influence of friendship in the workplace and person-Organization Fit on Organizational Citizenship Behavior through Job Satisfaction as an intervening variable in the village apparatus of Kebumen District. The population in this study were all employees of the Kebumen District apparatus with 150 employees. The instrument used in this study is a questionnaire to obtain the primary data needed. The research method is quantitative analysis, data obtained based on answers from respondents on the questionnaire, analyzed by statistical techniques of multiple linear regression analysis, regression models were tested with classical assumptions in order to meet the requirements and feasible to be used to predict the influence of independent variables on the dependent variable. The results of regression calculations are tested by the t test and coefficient of determination. The results of this study indicate that friendship variables in the workplace and PO-fit affect the Organizational Citizenship Behavior through Job Satisfaction in the Kebumen village apparatus. In this study, it is known that friendship in the workplace is the independent variable with the greatest influence on employee Organizational Citizenship Behavior compared to other independent variables.